Antioxidant and anti-inflammatory activities of cytisus multiflorus - Saraiva, Susana C. (2012)
Cytisus multiflorus(white spanish broom) is a plant used in folk medicine in the Iberian Peninsula, where it is claimed to have various health benefits. However, the usage is totally based on the available ethnopharmacological information, as no scientific data regarding its biological effects has been delivered. In this sense, is the aim of this work to contribute to the scientific knowledge of the antioxidant and anti-inflammatory properties of C. multiflorus. The extract was rich in phenolic compounds mainly chrysin-7-O-glycopyranoside and a dihydroxyflavone isomer of chrysin which accounted for 49.4±7.3 mg/g and 21.8±3.8 mg/g, respectively. The low EC50 values, determined by DPPH and reducing power assays, indicated that the C. multiflorus purified ethanolic extract has a high antioxidant capacity. Moreover, the extract did not cause cytotoxicity against RAW 264.7 macrophages for high concentrations and the treatment of this cell line with purified extract induced a significant decrease in the levels of NO. Overall, the gathered data suggests that C. multiflorus is in fact a good antioxidant and anti-inflammatory plant, as believed by the folk knowledge.